Landslide: a memoir? and ‘From the mouth of babes’: Considering memoir’s validity solely from a child narrator (or, sans adult narrator) - Kale, Amanda/AMK (2025)
This PhD thesis serves a dual purpose: a creative excerpt from Landslide, my (debated) ‘memoir’; alongside critical commentary on its specific writing process within the broader contexts of memoir, narratology, and child narration.